MPPT Tracking of Adaptive Lighting and Partial Shading in Photovoltaic Systems - QUAN Shao-li; PIAO Zhe-yong; CHEN Peng-hao; WANG Jing; SUN Yi-hao; LIU Wen-xia; LI Hai-yan; YANG Yan-hui; FU Meng-di (Journal of Harbin University of Science and Technology)
In order to solve the problem of inaccurate tracking of the maximum power point of the current high-performance tracking method was proposed. Firstly，the tracking principle of the proposed method was analyzed，and the discussion was carried out from the aspects of model structure，scanning process，duty cycle calculation，trigger conditions，etc. ，and theoretically analyzed that the proposed method can accurately track the global maximum value. Secondly，using simulation software，the proposed tracking method was compared with the current application of the more mature disturbance observation method and the conductance increment method. The two conditions of rapid light intensity change and partial shading were simulated，and the simulation results shows that this method is significantly better than the other two methods. Finally，a test platform was built to carry out the tracking test of the maximum power point of the system when the light intensity changes rapidly and partial shading. The test results again confirmed that the method proposed in this paper is both in tracking time and tracking efficiency. Better than the other two methods.